Sudden Bilateral Hearing Loss, Tinnitus, and Vertigo as Presenting Symptoms of Chronic Myeloid Leukemia. (October 2018) - Cass, Nathan D.; Gubbels, Samuel P.; Portnuff, Cory D. F.
Objectives: The objective was to describe a unique case of sudden bilateral hearing loss, tinnitus, and vertigo presenting as the first symptoms of chronic myeloid leukemia (CML). Methods: A patient case is discussed along with a review of associated literature. Results: A patient presented with sudden onset hearing loss, tinnitus, and vertigo, and was diagnosed with CML with an initial white blood cell (WBC) count of 555 000 per microliter. The proposed etiology of otologic symptoms is hyperleukocytosis. Serial audiograms showed minimal improvement in hearing despite reduction of WBC. Conclusion: In cases of bilateral, sudden onset sensorineural hearing loss, evaluation for systemic causes of otologic symptoms, including CML, should be considered.